The Qurʾān in History: Muhammad’s Message in Late Antiquity (Doctor Virtualis, 2022)
Late Antiquity describes a period of profound transformations that involved Europe, the Mediterranean world and the so-called Near East, from IV-V to VII-VIII centuries. This paradigm has now become widely used in Islamic studies, from Qurʾānic studies, where Angelika Neuwirth has extensively published in the past on the subject of the biblical underpinnings of the Qurʾānic revelation as a manifestation of late antique scripturalism, to historical studies related to the Qurʾān and pre-Islamic Arabia, as in Aziz al-Azmeh’s book The Emergence of Islam in Late Antiquity, which takes up the trend of scholarship established by Julius Wellhausen and Toufic Fahd. I completely agree with the need to put Islam and its historical, religious, philosophical birth and development in the context of the Late Antiquity, but what is at stake is to emphasize which themes made Islam a new religion with respect to Judaism and Christianity. This is the focus of the present paper which deals with: 1) a brief critical survey of the literature on Late Antiquity; 2) the relationship between the empires – Roman, Byzantine and Sasanid – of Late Antiquity and the triumph of monotheism; 3) the concept of hanifiyya. The conclusion is that the Qurʾānic message conveyed by Muhammad broke the history into two parts: before and after the coming of truth.
Keywords: Qur’ān; Muhammad; Late Antiquity; Monotheism